Psikhologicheskii analiz problemy odinochestva u grazhdan pozhilogo vozrasta, prokhodiashchikh sotsial'nuiu reabilitatsiiu v kompleksnom tsentre sotsial'nogo obsluzhivaniia naseleniia - Alieva V. R., Petrova E. R. (Psychology today: from theory to practice, 2024)
the data studied in the article are relevant, since understanding the psychological analysis of the problems of single elderly citizens undergoing social rehabilitation can give an idea of their mental health, social well-being and the effectiveness of rehabilitation programs adapted to their needs, which ultimately will contribute to improving the psycho-emotional state, strengthening care and support for this category of citizens.
Keywords: социальная реабилитация; одиночество; elderly citizens; loneliness; subjective feeling of loneliness; social rehabilitation; comprehensive social service center; граждане пожилого возраста; субъективное ощущение одиночества; комплексный центр социального обслуживания населения